Microbiological and Physicochemical Assessment of Untreated Borehole Water in Residential Areas of Kubang Kerian, Kelantan - Wan Nor Amilah, Wan Abdul Wahab; O Jah, Isatou; George Lojuyo, Gillian Steffy; Noor Izani, Noor Jamil (Malaysian Journal of Medical Sciences, 2025)
Background: Due to concerns regarding the quality of municipal water in Kubang Kerian, Kelantan, Malaysia, many residents rely on borehole water, which is often untreated and potentially unsafe. In this study, we assess the microbiological and physicochemical quality of borehole water from household outdoor sources and examine potential risk factors in this regard, including borehole depth and the proximity to sewage systems. Methods: Thirty untreated borehole water samples were collected from residential households and analysed using standard microbiological and physicochemical techniques. Heterotrophic plate count (HPC), total coliforms, faecal coliforms and Escherichia coli were determined. Physicochemical parameters included pH, turbidity and free residual chlorine. Associations between microbial quality and borehole characteristics were assessed using Fisher’s exact test. Results: While 70% of samples met the Malaysian Raw Water Quality Criteria (RWQC), 30% showed microbiological contamination, including three with E. coli. All samples had acceptable pH and turbidity levels, though residual chlorine was absent. None of the boreholes complied with the recommended minimum distance from sewage systems, and only four met the minimum depth standard. No significant associations were found between contamination and borehole depth or proximity to sewers (P > 0.05). Conclusion: Despite meeting physicochemical standards, a notable proportion of the borehole samples were microbiologically unsafe. These findings underscore the need for improved borehole construction practices, routine monitoring and public education to reduce waterborne health risks.